Dynamic Resource Management in Healthcare: A Case Study of Kubernetes-Based Platform Scaling - Mahitha Adapa, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of a large-scale Kubernetes-based healthcare platform implementation, demonstrating the transformative potential of cloud-native architecture in healthcare operations. The article examines the design, implementation, and operational outcomes of a dynamically scalable infrastructure serving millions of patients while maintaining strict regulatory compliance. Through detailed analysis of the platform's architecture, monitoring systems, and resource management mechanisms, this article provides insights into achieving operational excellence in healthcare IT infrastructure. The article reveals significant improvements in resource utilization efficiency, operational cost reduction, and system reliability through intelligent container orchestration. The implementation successfully addresses common healthcare infrastructure challenges while establishing a framework for maintaining HIPAA compliance in a cloud-native environment. This case study contributes to the growing body of knowledge on healthcare IT modernization and provides valuable insights for organizations seeking to implement similar solutions. The results demonstrate the viability and effectiveness of container orchestration technologies in healthcare settings, offering a blueprint for future implementations while highlighting key considerations for maintaining regulatory compliance and operational efficiency.
Keywords: Healthcare Infrastructure; Kubernetes Orchestration; Dynamic Scaling; HIPAA Compliance; Resource Optimization